Periferne vizije - Vidmar, Ksenija H. (Teorija in praksa, 2017)
The article investigates the Greek debt crisis in light of the most recent debates on the future of the EU. Special attention is paid to two aspects of the struggle for the EU integration after the austerity measures were implemented: the first, described in the text as the "Mediterranean effect", which appears as a legitimation tool for the measures, and the second, which belongs to broader intellectual debates on neoliberalism in the EU. Both aspects are inserted in the analysis of the transformative processes on the EU periphery, with an emphasis on a comparative look at the reception of the crisis in Spain, Greece and Slovenia. The key thesis is that fighting neoliberalism cannot rely on the modern political conceptual toolkit, including class struggle, without initially addressing the question of the subject in neoliberalism.
Keywords: Denarna kriza; Grčija; Greece; grška kriza; Mediteran; Monetary crisis; neoliberalni subjekt; periferija; revščina; varčevanje